MRI‐defined sarcopenia predicts mortality in patients with chronic liver disease. (28th October 2020) - Beer, Lucian; Bastati, Nina; Ba‐Ssalamah, Ahmed; Pötter‐Lang, Sarah; Lampichler, Katharina; Bican, Yesim; Lauber, David; Hodge, Jacqueline; Binter, Teresa; Pomej, Katharina; Simbrunner, Benedikt; Semmler, Georg; et al.
Abstract: Background & Aims: To explore whether sarcopenia, diagnosed by an abbreviated magnetic resonance imaging (MRI) protocol is a risk factor for hepatic decompensation and mortality in patients with chronic liver disease (CLD). Methods: In this retrospective single‐centre study we included 265 patients (164 men, mean age 54 ± 16 years) with CLD who had undergone MRI of the liver between 2010 and 2015. Transverse psoas muscle thickness (TPMT) was measured on unenhanced and contrast‐enhanced T1‐weighted and T2‐weighted axial images. Sarcopenia was defined by height‐adjusted and gender‐specific cut‐offs in women as TPMT < 8 mm/m and in men as TPMT < 12 mm/m respectively. Patients were further stratified into three prognostic stages according to the absence of advanced fibrosis (FIB‐4 < 1.45, non‐advanced CLD), compensated‐advanced CLD (cACLD) and decompensated‐advanced CLD (dACLD). Results: The inter‐observer agreement for the TPMT measurements (κ = 0.98; 95% confidence interval [95% CI]:0.96‐0.98), as well as the intra‐observer agreement between the three image sequences (κ = 0.99; 95% CI: 0.99‐1.00) were excellent. Sarcopenia was not predictive of first or further hepatic decompensation. In patients with cACLD and dACLD, sarcopenia was a risk factor for mortality (cACLD: hazard ratio (HR):3.13, 95% CI: 1.33‐7.41, P  = .009; dACLD:HR:2.45, 95% CI: 1.32‐4.57, P  = .005) on univariate analysis. After adjusting for the model of end‐stage liver disease (MELD) score, albumin and evidence of clinical significant portal hypertension, sarcopenia (adjusted HR: 2.76, 95% CI: 1.02‐7.42, P  = .045) remained an independent risk factor for mortality in patients with cACLD. Conclusion: Sarcopenia can be easily evaluated by a short MRI exam without the need for contrast injection. Sarcopenia is a risk factor for mortality, especially in patients with cACLD.